Semi-empirical potentials for CuI - Dalgic, SS; Gurbuz, H; Caliskan, M; Ozgec, O (NATL INST OPTOELECTRONICS, 2005)
We have investigated the prospects for developing semi-empirical model potentials for use in the studies of structural properties of CuI with integral equation theories. The point of view adopted requires that only short range two atom and three atom interactions appear. A three-body potential of Tersoff has been tasted with the hypernetted chain integral equation by calculating the pair correlation function for CuI at 710 K. The two-body and three-body Kohen-Tully-Stillinger empirical interatomic potential has been applied. The structural results of liquid CuI have been compared with experiment and those obtained by rigid ion potentials.
Keywords: semi-empirical potentials; CuI; structure; MOLECULAR-DYNAMICS SIMULATION; COMPUTER-SIMULATION; IONIC-CONDUCTION; PAIR POTENTIALS; SILICON; METALS; CUBR; CUCL; COORDINATION; TRANSITION; Materials Science; Optics; Physics